Frictional behaviour of imidazolium sulfate ionic liquid additives under mixed slide‐to‐roll conditions: Part 1 — Variation of mixtures with identical weight ratio of ionic liquid additive. (4th December 2014) - Pejaković, V.; Kalin, M.
Abstract: Ionic liquids are getting increased attention due to their potential use as additives or lubricants. One of parameters that influence their performance is anion alkyl chain length. Three chain lengths in imidazolium sulfate ionic liquids were varied in three different types of tests in order to study the friction performance in all lubrication regimes at different shear rates. Results show significant effect of alkyl chain length on friction behaviour and surface topography. The shortest chain length ionic liquid had the poorest friction performance whilst longer alkyl chain lengths performed significantly better, which was evidenced by the electrical contact resistance. Although friction behaviour was not generally reduced with ionic liquid mixtures, clear tribological improvement was observed in high shear conditions depending on alkyl chain length. Atomic force microscopy (AFM) analysis revealed correlation between ionic liquid chemistry and surface topography of samples after the experiments, with significantly increased roughness for short chain ionic liquid mixture. Copyright © 2014 John Wiley & Sons, Ltd.